Malaria in Eswatini, 2012–2019: a case study of the elimination effort - Theresia Estomih Nkya; Ulrike Fillinger; Makhoselive Dlamini; Onyango P. Sangoro; Rose Marubu; Zulisile Zulu; Emmanuel Chanda; Clifford Maina Mutero; Quinton Dlamini (Malaria Journal, 2021)
Abstract Eswatini was the first country in sub-Saharan Africa to pass a National Malaria Elimination Policy in 2011, and later set a target for elimination by the year 2020. This case study aimed to review the malaria surveillance data of Eswatini collected over 8 years between 2012 and 2019 to evaluate the country’s efforts that targeted malaria elimination by 2020. Coverage of indoor residual spraying (IRS) for vector control and data on malaria cases were provided by the National Malaria Programme (NMP) of Eswatini. The data included all cases treated for malaria in all health facilities. The data was analysed descriptively. Over the 8 years, a total of 5511 patients reported to the health facilities with malaria symptoms. The case investigation rate through the routine surveillance system increased from 50% in 2012 to 84% in 2019. Incidence per 1000 population at risk fluctuated over the years, but in general increased from 0.70 in 2012 to 1.65 in 2019, with the highest incidence of 3.19 reported in 2017. IRS data showed inconsistency in spraying over the 8 years. Most of the cases were diagnosed by rapid diagnostic test (RDT) kits in government (87.6%), mission (89.1%), private (87%) and company/industry-owned facilities (84.3%), either singly or in combination with microscopy. Eswatini has fallen short of achieving malaria elimination by 2020. Malaria cases are still consistently reported, albeit at low rates, with occasional localized outbreaks. To achieve elimination, it is critical to optimize timely and well-targeted IRS and to consider rational expansion of tools for an integrated malaria control approach in Eswatini by including tools such as larval source management, long-lasting insecticidal nets (LLINs), screening of mosquito house entry points, and chemoprophylaxis. The establishment of rigorous routine entomological surveillance should also be prioritized to determine the local malaria vectors’ ecology, potential species diversity, the role of secondary vectors and insecticide resistance.